Desenvolvimento de vacinas inativadas contra a rinotraqueíte infecciosa bovina e a diarréia bovina a vírus - Simone Alencar Renault (2002)
We developed two combined inactivated vaccines against infectious bovine rhinotracheitis (IBR) and Bovine Virus Diarrhea (BVD) and two monovalent against IBR using as adjuvant, aluminum hydroxide emulsion and an oil / water (Emulsigen ® - MVP Laboratories) with the same concentrations of antigens. We developed a multiple emulsion adjuvant Oil / Water / Water (EM - A / O / A) for use in inactivated vaccines against these viruses. IN the stable had destabilized the structure as components of vaccines were added. Each vaccine was tested by its power from the Serum neutralizing immunization of five rabbits. The results were compared with those of rabbits vaccinated with two polyvalent vaccines commercially available in Brazil. There was no statistically significant difference (p 0.05) between vaccines, with regard to the adjuvant used. The combined vaccine with adjuvant Emulsigen ® was tested in cattle under the rules of "Code of Federal Regulation" and induced antibody levels sufficient to protect cattle in accordance with the standards and with data from the literature.